Pandemic, War, Natural Calamities, and Sustainability: Industry 4.0 Technologies to Overcome Traditional and Contemporary Supply Chain Challenges - Abirami Raja Santhi; Padmakumar Muthuswamy (Logistics, 2022)
Background: The supply chain ecosystem is becoming fragile and difficult to manage due to the complexities in its interlinked functions such as planning, procurement, production, logistics, distribution, and sales. Recently, organizations have started embarking on “Industry 4.0 technologies”, a name used to denote transformative modern-day technologies such as Artificial Intelligence, Machine Learning, automation and robotics, Internet of Things, Big Data Analytics, Blockchain, and so on to make faster decisions, optimize current practices, provide end-to-end transparency, increased collaboration, and superior warehouse management, which can collectively make it an “Intelligent supply chain”. However, a comprehensive understanding of the subject is required to understand the benefits and challenges of adopting them. Methods: Hence, the article aims to systematically review the literature to identify various challenges associated with supply chain management and provide an overview of the role of Industry 4.0 technologies in addressing them. In addition to traditional complexities, the uncertainties arising from contemporary challenges such as the COVID-19 pandemic, war, natural calamities, and difficulties businesses face in developing and adopting sustainable business practices. Results and Conclusions: The study shows that although it is hard to predict the level of disruptions during any global events, it is possible to be prepared through Industry 4.0 technologies that can give agility, transparency, and resilience to the supply chain.